Legal Perspectives on Small-Scale Infrastructure Development Through Public-Private Partnerships: A Development Law Analysis - Kurdi, Kurdi; Amalia, Prita; Wardhana, Yuki M.A (Jurnal Hukum Magnum Opus, 2025)
This study aims to analyze the implementation of infrastructure development in Indonesia using the Public-Private Partnership (PPP) scheme from the perspective of development law as proposed by Prof. Dr. Mochtar Kusumaatmadja. Infrastructure development is crucial for achieving national development goals and improving public welfare, yet it often faces challenges such as bureaucracy and funding. The PPP scheme offers a solution by integrating the public and private sectors, as well as sharing risks to enhance the effectiveness and efficiency of infrastructure projects. This research employs a normative juridical method to examine regulations related to PPP, specifically Presidential Regulation Number 38 of 2015, and a conceptual approach to understanding the development law theory proposed by Kusumaatmadja. This theory emphasizes the role of law as a tool for reform and social development, with two main dimensions: order and regulation, and effective governance. The study finds that the PPP scheme aligns with the principles of development law theory, focusing on sustainable development, orderliness, and adherence to international practices. Additionally, the PPP scheme demonstrates a close relationship with national legal development, supporting the implementation of infrastructure projects. These findings are expected to provide insights for the more effective development and application of PPP in the context of development law in Indonesia